PERBEDAAN PENGGUNAAN SOFTWARE STATISTIKA MINITAB, SPSS, SAS DAN OSS STATISTIKA–R DALAM PEMBELAJARAN METODE ANALISIS REGRESI BERGANDA DENGAN PEMILIHAN MODEL TERBAIK MENGGUNAKAN METODE STEPWISE - Azwar Habibi (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2013)
Regression analysis is a statistical analysis that aims to model the relationship between independent variables with the dependent variable. In the regression analysis is one method often used to select the best regression model of stepwise regression method. The purpose of this paper is to apply the best selection of regression models with stepwise method to compare data HBAT and stepwise regression method with the program package Minitab, SPSS, SAS and R. Thus, it can be concluded in principle can be shown to the interpretation of multiple linear regression analysis with selection of the best models using the Stepwise method using MINITAB statistical package, SPSS, SAS and R. Thus, to produce the best model . However, the advan tages and deficiency obtained the statistical package suitable for Stepwise regression analysis was SPSS and MINITAB, because this package is specially designed for the social sector in appropriate regression analysis. Because its use is more easily done because the menu based. SAS package is the most comprehensive software suitable for all types of existing analytical methods in statistics, but its use is very difficult because the command line rather than the menu based. While for interpretation using the R package output information in Stepwise regression analysis is easy and is complete so that it can be used in Stepwise regression analysis. Thus, the authors suggested using R packages in Stepwise regression analysis even more is the command line, but, in its use for the stepwise regression analysis commands are easy to do and produce output that is easy to understand.Keywords: Regression Analysis, Stepwise Regression Method, Minitab, R, SAS, SPSS.